Question
upstudy study bank question image url

3. Find all solutions of the equation below. \( 5^{5-2 x}=5^{6 x-3} \)

Ask by Savage Ward. in the United States
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( x=1 \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

The Deep Dive

To solve the equation \( 5^{5-2 x}=5^{6 x-3} \), we can take advantage of the property that if the bases are the same, then the exponents must be equal. Therefore, we set the exponents equal to each other: \[ 5 - 2x = 6x - 3 \] Next, we will combine like terms. Start by adding \( 2x \) to both sides: \[ 5 = 8x - 3 \] Now, add \( 3 \) to both sides: \[ 8 = 8x \] To isolate \( x \), divide both sides by \( 8 \): \[ x = 1 \] Thus, the solution to the equation is \( x = 1 \). To verify, substitute \( x \) back into the original equation: For \( x = 1 \): \[ 5^{5-2(1)} = 5^{6(1)-3} \] \[ 5^{5-2} = 5^{6-3} \] \[ 5^3 = 5^3 \] This confirms our solution is correct! Therefore, the only solution is \( x = 1 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy